2006
DOI: 10.1038/nn1677
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent regulation of inhibitory synaptic transmission in hippocampal neurons

Abstract: Neural activity regulates the number and properties of GABAergic synapses in the brain, but the mechanisms underlying these changes are unclear. We found that blocking spike activity globally in developing hippocampal neurons from rats reduced the density of GABAergic terminals as well as the frequency and amplitude of miniature inhibitory postsynaptic currents (mIPSCs). Chronic inactivity later in development led to a reduction in the mIPSC amplitude, without any change in GABAergic synapse density. By contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
201
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(222 citation statements)
references
References 48 publications
17
201
1
Order By: Relevance
“…To address such a possibility, one would need to block either activity or neurotransmission, but not both. Recent studies have demonstrated that neither hyperpolarization nor reducing spike rate in the postsynaptic cell leads to compensatory changes in mPSC amplitude as would be predicted by the cell activity model (8,(16)(17)(18)(19). In those studies, the release and binding of neurotransmitters to their receptors was not altered, and thus the results are consistent with the neurotransmitter model.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…To address such a possibility, one would need to block either activity or neurotransmission, but not both. Recent studies have demonstrated that neither hyperpolarization nor reducing spike rate in the postsynaptic cell leads to compensatory changes in mPSC amplitude as would be predicted by the cell activity model (8,(16)(17)(18)(19). In those studies, the release and binding of neurotransmitters to their receptors was not altered, and thus the results are consistent with the neurotransmitter model.…”
mentioning
confidence: 60%
“…Once GABA A transmission is no longer depolarizing, it may not be able to trigger the same downstream cascades, and the role of triggering compensatory quantal changes may be transferred to AMPAergic transmission. In four separate studies (in vitro and in vivo), activity was reduced in only the postsynaptic cell by expression of a potassium channel, whereas neurotransmitter release by the cell inputs remained intact and presumably unaltered (16)(17)(18)(19). Although some of these studies reported a compensatory change in probability of release, none of them observed the expected increase in quantal amplitude.…”
Section: Discussionmentioning
confidence: 98%
“…Under conditions of chronic activity blockade in neuronal and organotypic cultures from hippocampus, the amount of inhibition and density of GABAergic terminals were reported to decrease (Marty et al, 2000;Hartman et al, 2006). In contrast, chronic activity or repetitive activation such as occurs with kindling has been shown to lead to a strengthening of inhibitory synaptic inputs, an enlargement of apposition zones and an increase in the number of GABA A receptors at inhibitory synapses, detected both with light microscopy and EM (Nusser et al, 1998;Marty et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…'s of controls and axotomized samples. We estimated requisite samples size for recordings of spontaneous postsynaptic currents by assuming a doubling or halving of mEPSC or mIPSC parameters following axotomy in correlation with the magnitude of changes observed in our analysis of spine numbers, presynaptic release data, and based on similar effect sizes being reported following synaptic activity blockade 64,65 . s.d.…”
Section: Discussionmentioning
confidence: 99%